VD_FINDINFO AI 44/12 - 11/2014 vom 28. Januar 2014 - VD Tribunal cantonal (2014)
ATTEINTE À LA SANTÉ PSYCHIQUE, DROIT À LA PRESTATION D'ASSURANCE, DÉBUT | 29 al. 2 Cst., 28 LAI, 4 al. 1 LAI, 49 LPGA, 7 LPGA, 8 LPGA, 23 LPP, 93 al. 1 let. a LPA-VD